Role of radical cations in aromatic hydrocarbon carcinogenesis. - Cavalieri, E (1985)
Carcinogenic activation of polycyclic aromatic hydrocarbons (PAH) involves two main pathways: one-electron oxidation and monooxygenation. One-electron oxidation produces PAH radical cations, which can react with cellular nucleophiles. Results from biochemical and biological experiments indicate that only PAH with ionization potentials below ca. 7.35 eV can be metabolically activated by one-electron oxidation. In addition, the radical cations of carcinogenic PAH must have relatively high charge localization to react effectively with macromolecules in target cells. Metabolic formation of PAH quinones proceeds through radical cation intermediates. Binding of benzo[a]pyrene (BP) to mouse skin DNA occurs predominantly at C-6, the position of highest charge localization in the BP radical cation, and binding of 6-methyl BP to DNA in mouse skin yields a major adduct with the 6-methyl group bound to the 2-amino group of deoxyguanosine. Studies of carcinogenicity by direct application of PAH to rat mammary gland indicate that only PAH with ionization potentials low enough for activation by one-electron oxidation produce tumors in this target tissue. These constitute some of the results which provide evidence for the involvement of one-electron oxidation in PAH carcinogenesis.